Target cell availability, rather than breast milk factors, dictates mother-to-infant transmission of SIV in sooty mangabeys and rhesus macaques. - Ann Chahroudi (Public Library of Science (PLoS), 2014)
Mother-to-infant transmission (MTIT) of HIV is a serious global health concern, with over 300,000 children newly infected in 2011. SIV infection of rhesus macaques (RMs) results in similar rates of MTIT to that of HIV in humans. In contrast, SIV infection of sooty mangabeys (SMs) rarely results in MTIT. The mechanisms underlying protection from MTIT in SMs are unknown. In this study we tested the hypotheses that breast milk factors and/or target cell availability dictate the rate of MTIT in RMs (transmitters) and SMs (non-transmitters). We measured viral loads (cell-free and cell-associated), levels of immune mediators, and the ability to inhibit SIV infection in vitro in milk obtained from lactating RMs and SMs. In addition, we assessed the levels of target cells (CD4+CCR5+ T cells) in gastrointestinal and lymphoid tissues, including those relevant to breastfeeding transmission, as well as peripheral blood from uninfected RM and SM infants. We found that frequently-transmitting RMs did not have higher levels of cell-free or cell-associated viral loads in milk compared to rarely-transmitting SMs. Milk from both RMs and SMs moderately inhibited in vitro SIV infection, and presence of the examined immune mediators in these two species did not readily explain the differential rates of transmission. Importantly, we found that the percentage of CD4+CCR5+ T cells was significantly lower in all tissues in infant SMs as compared to infant RMs despite robust levels of CD4+ T cell proliferation in both species. The difference between the frequently-transmitting RMs and rarely-transmitting SMs was most pronounced in CD4+ memory T cells in the spleen, jejunum, and colon as well as in central and effector memory CD4+ T cells in the peripheral blood. We propose that limited availability of SIV target cells in infant SMs represents a key evolutionary adaptation to reduce the risk of MTIT in SIV-infected SMs.